2017
DOI: 10.1016/s0140-6736(17)32016-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disability among elderly people in the occupied Palestinian territory: a cross-sectional study

Abstract: Background From the 2011 Palestinian Center Bureau of Statistics, disability is defined as long-term physical, mental, intellectual, or sensory impairment that can hinder full and effective participation in society; disability among elderly people has become a major public health concern in recent years. More than 1 billion people live with disability worldwide. In the occupied Palestinian territory, disability in elderly people is still not well understood. This study aims to assess the prevalence of disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…A previous study, conducted in São Paulo [ 13 ], found the prevalence of global disability to be 62.2%, higher than that observed in the present study, although that study included individuals ≥65 years of age, rather than ≥60 years of age as in the present study. Similarly, in São Paulo and Manaus, the prevalence of global disability was higher than that reported in studies investigating younger populations [ 5 , 23 , 25 , 35 ], which is to be expected because disability is age dependent [ 12 , 20 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous study, conducted in São Paulo [ 13 ], found the prevalence of global disability to be 62.2%, higher than that observed in the present study, although that study included individuals ≥65 years of age, rather than ≥60 years of age as in the present study. Similarly, in São Paulo and Manaus, the prevalence of global disability was higher than that reported in studies investigating younger populations [ 5 , 23 , 25 , 35 ], which is to be expected because disability is age dependent [ 12 , 20 ].…”
Section: Discussionmentioning
confidence: 95%
“…Within the elder population, the prevalence of disability is higher among women, the oldest age brackets, individuals with a lower level of education, and residents of low- and middle-income countries (LMICs), as demonstrated by studies conducted in several countries in Europe, Asia, Africa, the Americas, and the Middle East [ 5 , 8 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Knowing the functional status of the elder population is important to identify the most vulnerable members and their health needs.…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, as mulheres e os idosos mais velhos são os grupos populacionais com maior prevalência de incapacidade funcional, segundo estudos realizados em vários países da Europa, Ásia, África, Américas e Oriente Médio (Almazán-Isla et al, 2014, Biritwun et al, 2016, Katta et al, 2017, Naidoo et al, 2017, Jasser et al, 2017, Adib-Hajbaghery, 2011, Ćwirlej-Sozańska et al, 2018, Almazán-Isla et al, 2017Rodrigues et al, 2009;Hosseinpoor et al, 2012). Estudos nacionais e internacionais associaram a incapacidade funcional ao aumento da idade, baixa renda e menor escolaridade (Alves, 2010;Silva, 2013;Van den Brink et al, 2003;Berkman et al, 1989;Graciani et al, 2004;Alves et al, 2008;Huisman et al, 2003;Alves & Rodrigues, 2005;Jasser et al, 2017;Courtney-Long, 2015). Lima-Costa et al, 2007).…”
Section: Incapacidade Funcional E Características Sociodemográficasunclassified
“…Alguns estudos compararam a prevalência de incapacidade funcional entre países e atribuíram suas diferenças às características populacionais (Sousa et al, 2009;Gomez-Olive et al, 2017). Dentro os idosos, a prevalência de incapacidade funcional foi geralmente maior entre as mulheres, as faixas etárias mais velhas, indivíduos com menor nível de escolaridade, com mais comorbidades e residentes em países de renda média e baixa, como demonstrado por estudos realizados em países da Europa, Ásia, África, Américas e Oriente Médio (Rodrigues et al, 2009;Sousa et al, 2009;Adib-Hajbaghery, 2011;Pedro-Cuesta et al, 2011;Hosseinpoor et al, 2012;Silva et al 2013, Almazán-Isla et al, 2014Courtney-Long, 2015;Biritwun et al, 2016;Almazán-Isla et al, 2017;Argyriou et al, 2017;Gomez-Olive et al, 2017;Jasser et al, 2017;Katta et al, 2017;Naidoo et al, 2017;Waterhouse et al, 2017;Ćwirlej-Sozańska et al, 2018;Giacomin et al, 2018 (Barros et al, 2006).…”
Section: A Estratégia Saúde Da Família No Brasilunclassified
See 1 more Smart Citation